Incêndios florestais na comarca de Uberaba nos anos de 2017 e 2018: aspectos legais e da distribuição espacial - PENA, Felipe Fiochi (2019)
Forest fires are an environmental problem in Brazil, although there is abundant legislation regarding the prohibition of the indiscriminate use of fire, illegal use is recurrent and has great intensity in the Cerrado biome. This study aims to contribute to the current understanding of environmental legislation and the efficiency of monitoring systems applied to forest fires, as well as to analyze and evidence that land use changes can be identified through the occurrence of anthropogenic burning. In this sense, changes in land use and occupation in the Uberaba district were analyzed through remote sensing of official images and data from 2017 to 2018. Official data provided by the 8th Military Firefighters Battalion are exposed. of the Fire Department of Minas Gerais, regarding the records of fires in the rural area of the Uberaba County in the aforementioned years as: the main types of vegetation affected by the fire, the probable causes of the fires, as well as locations and periods of the year with the highest recurrences. The results show that nearly 90% (ninety percent) of the records were considered inconclusive as to the actual causes, making law enforcement and accountability of violators difficult. In addition, with the use of Google Earth Engine (GEE) it was found that the hypothesis raised is true, since in all municipalities studied more than 50% (fifty percent) of occurrences are related to land use change.